ZNF423: A New Player in Estrogen Receptor-Positive Breast Cancer - Bond, Heather M.; Scicchitano, Stefania; Chiarella, Emanuela; Amodio, Nicola; Lucchino, Valeria; Aloisio, Annamaria; Montalcini, Ylenia; Mesuraca, Maria; Morrone, Giovanni (Frontiers in Endocrinology, 2018)
Preventive therapy can target hormone responsive breast cancer by treatment with selective estrogen receptor modulators (SERMs) and reduce the incidence of breast cancer. Genome wide association studies have identified single nucleotide polymorphisms (SNPs) with relevant predictive values, SNPs in the ZNF423 gene were associated with decreased risk of breast cancer during SERM therapy, and SNPs in the Cathepsin O gene with an increased risk. ZNF423 which was not previously associated with breast cancer is a multifunctional transcription factor known to have a role in development, neurogenesis and adipogenesis, and is implicated in other types of cancer. ZNF423 is transcriptionally controlled by the homolog ZNF521, EBF transcription factor, epigenetic silencing of the promoter by CpG island hyper-methylation, and also by ZNF423 itself in an auto-regulatory loop. In breast cancer cells, ZNF423 expression is found to be induced by estrogen, dependent on the binding of the estrogen receptor and calmodulin-like 3 to SNPs in ZNP423 intronic sites in proximity to consensus estrogen response elements. ZNF423 has also been shown to play a mechanistic role by trans-activating the tumor suppressor BRCA1 and thus modulating the DNA damage response. Even though recent extensive trial studies did not classify these SNPs with the highest predictive values, for inclusion in polygenic SNP analysis, the mechanism unveiled in these studies has introduced ZNF423 as a factor important in the control of the estrogen response. Here, we aim at providing an overview of ZNF423 expression and functional role in human malignancies, with a specific focus on its implication in hormone-responsive breast cancer.